Tawny Owl Strix aluco as an indicator of Barn Owl Tyto alba breeding biology and the effect of winter severity on Barn Owl reproduction. (April 2014) - Chausson, Alexandre; Henry, Isabelle; Ducret, Bertrand; Almasi, Bettina; Roulin, Alexandre; Sergio, Fabrizio
<x xml:space="preserve">Abstract</x> In the temperate zone, food availability and winter weather place serious constraints on European Barn Owl Tyto alba populations. Using data collected over 22 years in a Swiss population, we analysed the influence of early pre‐breeding food conditions and winter severity on between‐year variations in population size and reproductive performance. To estimate pre‐breeding food conditions, we attempted a novel approach based on an index that combines Tawny Owl Strix aluco reproductive parameters and the occurrence of wood mice Apodemus sp. in their diet. Tawny Owls breed earlier in the season than Barn Owls and are strongly dependent on the abundance of wood mice for breeding. This index was strongly positively associated with the number of breeding pairs and early breeding in the Barn Owl. Winter severity, measured by snow cover and low temperatures, had a pronounced negative influence on the size of the breeding population and clutch size. Food conditions early in the breeding season and winter severity differentially affect the Barn Owl life cycle. We were able to use aspects of the ecology and demography of the Tawny Owl as an indicator of the quality of the environment for a related species of similar ecology, in this case the Barn Owl.